Age and oral health knowledge in relation to dental caries status in children aged 11-12 years - Gabriela Halim; Carera Iva Harryadi; Antonius Lucky Arnando (Indonesian Journal of Dental Medicine, 2026)
Background: Dental caries remains one of the most prevalent oral diseases among school-aged children and continues to be a major public health concern. In Indonesia, Basic Health Research reported that 92.6% of children experience oral health problems, with dental caries being the most common condition. Although oral health knowledge is considered an important factor in caries prevention, its relationship with dental caries status remains inconsistent. Purpose: To analyze the age and oral health knowledge in relation to dental caries status among 11–12-year-old students. Methods: An analytical observational study with a cross-sectional design was conducted among 50 students aged 11–12 years. Oral health knowledge was assessed using 10 multiple-choice questions questionnaire and categorized as good, moderate, or poor. Dental caries status was evaluated through clinical examination using the DMF-T index based on the WHO criteria and classified into low and high categories. Data were analyzed using the Chi-square test with a significance level of p<0.05. Results: Most students demonstrated moderate oral health knowledge (64%) and low caries status (86%). No significant association was found between age and dental caries status (p = 0.86). or between oral health knowledge and dental caries status (p > 0.05). Students with good oral knowledge showed lower odds of high caries status (OR = 0.64), although the association was not statistically significant. Conclusion: Age and oral health knowledge were not significantly associated with dental caries status among students aged 11-12 years. Other factors may contribute to the development of dental caries in school-aged children.